YOSHLARNI IJODIY FIKRLASHGA O‘RGATISH: INTERFAOL METODLARNING AHAMIYATI VA SAMARADORLIGI - Yo’ldoshev Jo’rabek, Boboyev Nodir (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines interactive methods that serve to develop creative thinking and ways to effectively implement them. The article emphasizes the relevance of teaching schoolchildren creative thinking, the importance and effectiveness of interactive methods. Important methods in modern education have been tested in practice - problem based learning, brainstorming, clustering and role-playing games. The results show that interactive methods are highly effective in developing independent thinking and creative approaches in young people.